2014
DOI: 10.1002/app.41329
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene/1‐hexene copolymerization with supported Ziegler–Natta catalysts prepared by immobilizing TiCl3(OAr) onto MgCl2

Abstract: Five titanium complexes TiCl3(OAr) (Ar = C6H5, 2,6‐Me2C6H3, 2,6‐i‐Pr2C6H3, 2,6‐t‐Bu2C6H3, 4‐Me‐2,6‐t‐Bu2C6H3) were immobilized, respectively, on MgCl2 in semibatch reaction to form supported catalysts for olefin polymerization. Comparing with the catalysts prepared by immobilizing TiCl3(OAr) onto MgCl2 in batch reaction, the catalysts prepared by semibatch reaction have lower titanium content and higher ArO/Ti ratio. The aryloxy‐containing catalysts studied in this work showed higher ethylene/1‐hexene cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Subsequent addition of the monomer solution to the catalysttethered particles resulted in grafted polycyclooctene (PCO-g-SiO 2 , 4) . After a mild hydrogenation, the grafted polymer was transformed into linear polyethylene (5). A series of samples was made according to this procedure, and the physical and chemical data for these samples is shown in Table 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent addition of the monomer solution to the catalysttethered particles resulted in grafted polycyclooctene (PCO-g-SiO 2 , 4) . After a mild hydrogenation, the grafted polymer was transformed into linear polyethylene (5). A series of samples was made according to this procedure, and the physical and chemical data for these samples is shown in Table 1.…”
mentioning
confidence: 99%
“…Despite the commercial relevance and excellent properties of PE, there are few examples of polyethylene nanocomposites stemming from the synthetic barriers involved in grafting PE on a nanosurface. Commercially, polyethylene is produced by reacting ethylene gas with a Ziegler–Natta catalyst comprised of a transition metal complex (commonly titanium or zirconium) in combination with an organoalumnium cocatalyst (e.g., triethylaluminum). The chain growth polymerization occurs through olefin insertion between the metal center and a coordinated alkyl group. These polymerizations generally result in polymers with a broad molecular weight distribution but can also produce polyolefins with excellent stereochemical fidelity (e.g., isotactic polypropylene). , Fundamental investigation of nanocomposites has shown that control of chain graft density and molecular weight is essential for obtaining predictable nanofiller dispersion within a polymer matrix and for realizing the subsequent property enhancements. …”
mentioning
confidence: 99%
“…In the MWD curves of the polymers, shifting toward low-MW with increasing 1-hexene could be clearly seen like the MWD curves in Figure S5 in the Supporting Information. As mentioned by Yang et al [37] in copolymerization with ethylene as the main monomer, the strength of comonomer effects was much stronger in active centers producing low-MW polymer than those producing high-MW polymer, leading to a significant decrease in average MW of the whole polymer and broadening its MWD. MWD was clearly broadened with increasing 1-hexene concentration.…”
Section: Ethylene/1-hexene Copolymerization and Characterization Of Tmentioning
confidence: 93%
“…It is seen that the broad CCD of Z-N based PE resins needs to be improved. In the past two decades, many efforts have been devoted to improving the ethylene-α-olefin copolymerization performance of Z-N catalysts [10][11][12][13][14][15][16][17]. However, improvements in ethylene copolymer's CCD were not satisfactory in many of these efforts.…”
Section: Introductionmentioning
confidence: 99%